2020
DOI: 10.1186/s10020-020-00214-x
|View full text |Cite
|
Sign up to set email alerts
|

Markers of vitality in ovaries of transmen after long-term androgen treatment: a prospective cohort study

Abstract: Background Gender-affirming hormone therapy has been hypothesized to reduce the patient’s reproductive potential in transmen, although the exact long-term effects on future fertility are unknown. Methods In this prospective cohort study we aimed to evaluate ovaries of 20 transmen by using hormone serum levels, histomorphological analysis and fluorescence activated cells sorting (FACS) analysis – in order to assess the amount of vital cells. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
5
1
1
Order By: Relevance
“…In a recent prospective study, histopathological analysis using fluorescence-activated cell sorting was performed with the ovaries of transmen receiving gender-assigning hormone therapy. Results from the study showed that 88% of the ovarian cells showed normal cortical follicle distribution, which shows a disparity to previous pathological studies where most of the ovarian specimens had polycystic or atrophic attributes [ 21 ]. Adverse events and the effects of long-term testosterone exposure to ovarian tissue are still under study and research.…”
Section: Gender-affirming Therapy and Fertility Preservation Methods ...contrasting
confidence: 77%
“…In a recent prospective study, histopathological analysis using fluorescence-activated cell sorting was performed with the ovaries of transmen receiving gender-assigning hormone therapy. Results from the study showed that 88% of the ovarian cells showed normal cortical follicle distribution, which shows a disparity to previous pathological studies where most of the ovarian specimens had polycystic or atrophic attributes [ 21 ]. Adverse events and the effects of long-term testosterone exposure to ovarian tissue are still under study and research.…”
Section: Gender-affirming Therapy and Fertility Preservation Methods ...contrasting
confidence: 77%
“…The specific effect of androgens on the viability of ovarian tissue is unknown and discussed controversially [ 30 , 31 ]. Other studies indicate that a long-term androgen treatment does not seem to reduce the primordial follicle pool, and that ovaries of transmen represent an excellent source of tissue for research purposes [ 32 , 33 ]. We are aware, that the viability of ovarian tissue can only be determined after reimplantation, but using FACS analysis, we were able to demonstrate the viability of different cell types, which we regard as a strength of our study.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware, that the viability of ovarian tissue can only be determined after reimplantation, but using FACS analysis, we were able to demonstrate the viability of different cell types, which we regard as a strength of our study. Using FACS analysis in ovarian tissue is a relatively new methodical approach, which has been only rarely used, so far [ 33 , 34 ]. Evaluating ovarian tissue after vitrification by using morphological parameters and histologic analyses is the main focus of most studies, based on the assumption that morphological intact follicles are representative for the success of ovarian tissue re-transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…While average ovarian volume remained within normative values, increased duration of testosterone exposure was associated with decreased ovarian volume [36 && ]. In another histopathologic study of ovaries from transgender men with a median 17 months of testosterone exposure, fluorescence activated cell sorting analysis revealed the majority of ovarian cells to be vital (88%) with normal cortical follicle distribution visualized [37]. These findings are in contrast to earlier pathologic studies in which the majority of specimen exhibited polycystic or atrophic patterns [38,39].…”
Section: Masculinizing Hormones and Fertilitymentioning
confidence: 70%